Machine learning model evaluation on healthcare applications: A Review - Souza, Cezar Miranda Paula de; Barreto, Cephas Alves da Silveira; Macedo, Lhayana Vieira de; Brito, Bruna Alice Oliveira de; Targino, Victor Vieira; Betcel, Emanuel Costa; Almeida, Fernando Gomes de; Rodrigues, Arthur Andrade Galvíncio; Malaquias, Ramon Santos; Filho, Itamir de Morais Barroca (Seven Editora, 2023)
Machine Learning (ML) models have been applied to solve problems in various fields, which necessarily involves proper evaluation of models to ensure performance. Once deployed, ML models are subject to performance issues, such as those related to changes in data (drift). This type of issue has prompted efforts in model analysis and maintenance, as well as in continual learning, which seeks the ability to continuously learn from a (continuous) stream of data. Therefore, it’s important to understand and develop methodologies that can be used to evaluate ML models, making their use in real-world environments feasible. Amongst current areas of application for ML, one that stands out, in particular, is Machine Learning for Healthcare, especially in conjunction with Software for Decision Support of Medical Applications, which presents specific challenges for the evaluation and monitoring of models, particularly given that incorrect prediction or classification can lead to life-threatening situations. This paper presents a systematic literature review that aims at identifying state-of-the-art techniques for evaluating and maintaining ML models for healthcare in effective use in the real world. DOI:https://doi.org/10.56238/interdiinovationscrese-013